A case report on acute disseminated encephalomyelitis in adult - Bhavani, Dhomakonda; Shirisha, Boddu; Sushma, Gadila; Charitha, Mekala Sai (Indian Journal of Case Reports, 2025)
Acute disseminated encephalomyelitis (ADEM) is an uncommon immune-inflammatory syndrome that usually presents as a monophasic disorder with several neurological symptoms. ADEM is an inflammatory disease that damages the brain and spinal cord’s white matter by demyelinating it as a result of an immunological reaction. The majority of ADEM cases arise after a bacterial or viral illness, and it has been linked to both prior infections and vaccinations. High-dose intravenous glucocorticoids combined with immunosuppression are the first-line acute treatment for ADEM. A case of ADEM in a 42-year-old male is described.